Novel porous fly ash-containing geopolymers for pH buffering applications. (15th June 2016) - Novais, Rui M.; Buruberri, L.H.; Seabra, M.P.; Bajare, D.; Labrincha, J.A.
Abstract: In this work novel, porous biomass fly ash-containing geopolymers with high pH buffer capacity and tailored alkalis leaching were produced by using hydrogen peroxide as blowing agent. Results demonstrate that the geopolymers leaching rate can be controlled by the hydrogen peroxide content and by the solids-to-liquid ratio during geopolymers preparation. Total leaching of hydroxyl ions from the porous geopolymers ranged between 0.0104 and 0.0180 mol/(dm 3 g). Higher solids-to-liquid ratios promoted a gentler alkalis leaching from the geopolymers, while higher porosities shifted the initial pH towards higher values without compromising their buffering ability. The excellent ability to control pH over time shown by these novel geopolymers demonstrates their potential as pH regulators in applications where high buffer capacity is required. Furthermore the reuse of biomass fly ash in these innovative materials reduces the environmental footprint associated with this waste disposal. Graphical abstract: Highlights: Porous fly ash-containing geopolymers with high pH buffer capacity were developed. Total porosity and the solids-to-liquid ratio control the alkalis leaching. Geopolymers exhibiting narrow pH fluctuations (up to 0.92) over time were produced. Waste valorization by reuse of biomass fly ash.